PENERAPAN METODE AL-MIFTAH DALAM MENGEMBANGKAN KEMAMPUAN MEMBACA KITAB KUNING DI MADRASAH DINIYAH TAKMILIYAH ULA MIFTAHUL ULUM 1 TENGGULUNAN - Alfina Rahma Wati; Achmat Mubarok; Wiwin Fachrudin Yusuf (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low reading ability of students at Madrasah Diniyah Takmiliyah Ula Miftahul Ulum 1 Tenggulunan, particularly in mastering the rules of nahwu, sharaf, and reading unvocalized Arabic texts. In response to this problem, the madrasah implemented the al-Miftah method as a more practical, systematic, and easily understood learning approach. This study aims to: (1) describe the impelementation of the al-Miftah method in developing student’s ability to read kitab kuning at the Madrasah Diniyah Takmiliyah Ula Miftahul Ulum 1 Tenggulunan), and (2) identify the inhibiting and supporting factors in its implementation. This study used a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation. Then analyzed throught data condensation, data display, and conclusion drawing. Data validity was tested through triangulation. The results show that: (1) the implementation of the al-Miftah method was carried out systematically through the stages of planning, implementation, and evaluation. Planning include setting learning objectives, arranging materials progressively from volume 1 to volume 4, and implementing a teacher rotation strategy. The implementation of learning included reading nadzoman, takror, questions and answers, material delivery, tamrin, and evaluation. Evaluation was conducted through daily formative assesment and volume promotion examinations. (2) The inhibiting factors identified were low student engagement, suboptimal independent muraja’ah, student boredom, and variation in teacher competence, while the supporting factors were a structured teacher coaching system, supervision from the al-Miftah Sidogiri center, a competency-based teacher rotation strategy, and a progressively organized set of learning materials.